Operation IRAQI FREEDOM Decisive War, Elusive Peace - Perry, Walter L. (RAND Corporation, 2015)
Soon after Operation IRAQI FREEDOM began in March 2003, RAND Arroyo Center began a project, completed in January 2006, to produce an authoritative account of the planning and execution of combat and stability operations in Iraq and to recommend changes to Army plans, operational concepts, doctrine, and Title 10 functions. This report presents a broad overview of the study findings based on unclassified source material.